PPO.63 Patient safety in the nhs: the role of the coroner rule 43 in improving maternal safety. (9th June 2014) - Burrell, C
Abstract : Background: The UK CMACE Report 2006–2008 Top Ten Recommendations #9 and #10 highlighted the importance of investigating Serious Incidents and maternal death to establish an integrated safety-focused culture. With the increasing number of high-risk women with adverse fetal/maternal morbidities and mortalities, more cases are being referred to the Coroner. The Coroner provides an inquisitorial investigation when there is a sudden, suspicious, violent, unknown or unnatural death; this establishes who, how, when and where the deceased died [Coroner's Act 1988 section 11 (amended) and the Coroners Rules 1984 Rule 36 (amended)]. Method: This review looks at the duty of the Coroner as an external independent judiciary officer to promote patient safety in maternal heath, and highlights the Coroner's Rule 43. Results: - The role of the Coroner is increasingly improving maternal health, both by investigating a death, and to promote proactive patient safety by making recommendations to prevent a future death (Coroners Rule 43 amended). The Ministry of Justice 9th Coroners Rule 43 Report for England and Wales (June 2013) showed between 1/10/ 2012–31/03/2013 - There were 235 Rule 43 Reports, the highest number issued since 2008. Also 70 of the 111 Coroners districts issued Rule 43 Reports, the highest number issued since 2008. Conclusion: The UK CEMACE Report (2006–2008) highlighted significant sub-standard patient care, thus more cases will be referred to the Coroner. The Coroner continues to play an important role to improve safety in maternal health. With the record increase in Coroner's Rule 43 being issued, in the current medico-legal climate, patient safety remains of paramount importance.